The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5888/pcd11.130217
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Health-Related Internet Use Among African American Men, 2010

Abstract: Given the benefits of health-related Internet use, we examined whether sociodemographic, medical, and access-related factors predicted this outcome among African American men, a population burdened with health disparities. African American men (n = 329) completed an anonymous survey at a community health fair in 2010; logistic regression was used to identify predictors. Only education (having attended some college or more) predicted health-related Internet use (P < .001). African American men may vary in how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…In particular, the main pressure in performance assessment for doctors is the assessment of income generation [ 12 ], and doctors’ performance assessment shows the impact of the market-oriented reform of medical services, and patients’ perception of healthcare cost the impact of the demand side. The education level of patients shows to some extent the availability of health-related websites and other sources of medical information [ 40 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the main pressure in performance assessment for doctors is the assessment of income generation [ 12 ], and doctors’ performance assessment shows the impact of the market-oriented reform of medical services, and patients’ perception of healthcare cost the impact of the demand side. The education level of patients shows to some extent the availability of health-related websites and other sources of medical information [ 40 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…The high burden of health disparities experienced by African American men across chronic diseases (Thorpe et al, 2013), cancer (Mitchell, Watkins, & Modlin, 2013, Mitchell, Manning, Shires, Chapman, & Burnett, 2014; Mitchell, Thompson, Watkins, Shires, & Modlin, 2014), and mental health (Watkins, Hawkins, & Mitchell, 2015) outcomes has been documented in the literature. Health self-efficacy, a measure of one’s self-assurance in taking care of their own health (Marks, Allegrante, & Lorig, 2005), is a proximal and direct predictor of health behaviors, intentions, and outcomes and has been linked to improvements in chronic disability (Marks et al, 2005), physical activity (McAuley et al, 2006), diabetes management (Lee & Lin, 2009), and a host of other health-related outcomes.…”
Section: Background and Research Questionmentioning
confidence: 99%
“…Information technologies have the potential to lower these obstacles and make it easier for caregivers to obtain the assistance they require [ 180 ]. Studies have shown that older patients and African Americans are more likely to engage in telephone coaching contacts and have access to telephones compared to computers or Internet connections, which is a culturally sensitive concern for this intervention [ 204 ]. Telephonic interventions are chosen due to their low cost, convenience of use, and delivery of interventions.…”
Section: Risk Factors/susceptibility Of Ad In African Americansmentioning
confidence: 99%